INTERVIEW WITH ATTILA ILHAN “CAPTAIN” OF TURKISH LITERATURE - BEYİTOĞLU, Yahya Kemal (Atlas Journal, 2022)
Attila Ilhan, one of the unique artists of Turkish literature; although he wrote works in genres such as poetry, novels, essays and scenarios, he generally came to the fore with his poetry. Information about the world of thought of the artist, whose literary personality and intellectual aspect predominate, can be obtained from his works and interviews with him. For this purpose, this interview, which needs to be published; in 2003, it consists of the “Interview” section of the graduation thesis named “Istanbul Themes in Attila Ilhan’s Poems” prepared by us under the consultancy of Assoc. Dr. Mümtaz Sarıçiçek. In this interview, which was held two years before the poet’s death, questions were asked to the artist about “poetry and Istanbul”. In this context, it can be said that the article can be useful for researchers who will work on Turkish poetry in the Republican Period, Istanbul and Attila Ilhan. However, Attila Ilhan does not only express his views on poetry and Istanbul in this interview; He also conveyed his valuable thoughts and memories to us on subjects such as language, history and culture. The interview was held on February 5, 2003 at The Marmara Hotel with a voice recorder and with the help of our dear friend Gökhan Engin.